2010
DOI: 10.1111/j.1743-6109.2010.01882.x
|View full text |Cite
|
Sign up to set email alerts
|

Interrelationship of Sildenafil Treatment Effects on the Physiological and Psychosocial Aspects of Erectile Dysfunction of Mixed or Organic Etiology

Abstract: Introduction In a previous paper using mediation modeling, the direct and indirect effects of sildenafil on erection maintenance were demonstrated. Objective In an extension of this previous work, the historical psychosocial paradigm of ED, which focuses on performance anxiety, is tested by using mediation modeling to define the relationship of the physiological aspects (hardness and maintenance) and the associated psychosoci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
19
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 24 publications
(26 reference statements)
3
19
0
Order By: Relevance
“…Adverse events, such as priapism, visual disturbances, and hemodynamic change, which have been reported in studies of other PDE5 inhibitors, are thought to be related to the lack of stringent PDE5 specificity; although all of these agents are specific for the PDE5 isoenzyme, unintentional cross-reactivity may occur with other PDE isoenzymes, including inhibition of PDE6 and PDE11, which may lead to AEs. 20,[30][31][32][33][34] In this study, none of these types of events was reported, and there was only 1 report of blurred vision, supporting the high PDE5 specificity of avanafil.…”
Section: Discussionsupporting
confidence: 59%
“…Adverse events, such as priapism, visual disturbances, and hemodynamic change, which have been reported in studies of other PDE5 inhibitors, are thought to be related to the lack of stringent PDE5 specificity; although all of these agents are specific for the PDE5 isoenzyme, unintentional cross-reactivity may occur with other PDE isoenzymes, including inhibition of PDE6 and PDE11, which may lead to AEs. 20,[30][31][32][33][34] In this study, none of these types of events was reported, and there was only 1 report of blurred vision, supporting the high PDE5 specificity of avanafil.…”
Section: Discussionsupporting
confidence: 59%
“…These advanced, more complicated types of mediation models have also been used to more deeply understand PROs. 61,62 Other applications of mediation models with PROs can be found elsewhere. 63 Missing data are common for PRO data, especially when they are assessed over time, and are a separate issue from interpretation of PRO scores.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the results might have been influenced by several hidden clinical factors such as amelioration of anxiety or performance anxiety over the study period. 30 Based on an IIEF-5 cutoff score of 7 points, patients were divided into two groups, which were the responder and non-responder groups. There was a significant difference in the change in cognitive function between the two groups.…”
Section: Effect Of Repeated Dosing With Udenafil On Cognition Somatimentioning
confidence: 99%